2021
DOI: 10.24093/awej/covid.6
|View full text |Cite
|
Sign up to set email alerts
|

Devices and Platforms Used in Emergency Remote Learning and Teaching During Covid19: A Case of English Major Students in Saudi Arabia

Abstract: This study investigates the experiences of English major students at the College of Language and Translation (COLT) in King Saud University, Saudi Arabia, with Emergency Remote Learning and Teaching (ERLT) during the Covid-19 crisis. It focuses on the students’ preferences for devices and platforms, and gender differences influencing their choices. The study is of significance because it considers the student-centered learning approaches. The paper also seeks to answer the question as to the factors that lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The study findings showed that Zoom came first in students' preferences with 57.6%, and came Blackboard with 40.6%, and last were the other platforms. The results came in line with Al Shammari's (2021) finding and contrary to Ibrahim et al (2021). As for gender differences in the first question of platform preferences, the results indicated that female students preferred Zoom (66%), followed by Blackboard (32%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The study findings showed that Zoom came first in students' preferences with 57.6%, and came Blackboard with 40.6%, and last were the other platforms. The results came in line with Al Shammari's (2021) finding and contrary to Ibrahim et al (2021). As for gender differences in the first question of platform preferences, the results indicated that female students preferred Zoom (66%), followed by Blackboard (32%).…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, male students came with the same Zoom and Blackboard preferences with 49.3% each. These findings came were the opposite of the result of Al Shammari (2021), in which he found that women students chose Blackboard first with 58.7% against Zoom (40%), whereas men students were for Zoom (67.6%) against Blackboard (29.7%). The results here indicate a real need for one platform that has features of both LMSs and VCPs.…”
Section: Discussionmentioning
confidence: 61%
“…Gender differences exist in the preferences of using online platforms [ 19 ]. In another study in the USA, it was found that in the delivery of course content, age and gender had no significant effect [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to guarantee continuity of quality education during COVID-19 pandemic online delivery of courses has been initiated immediately at all academic levels of higher education institutions. All public universities in Saudi Arabia have adopted Blackboard as their major learning management system (Al Shammari, 2021).…”
Section: Introduction and Context Of The Researchmentioning
confidence: 99%